Hep Birlikte - Osseiran, Nejla (Turkey, 2016)
TThe civil war in Syria caused an inevitable refugee crisis. Millions left their homes behind to find refuge in neighboring and European countries. The main route to Europe was crossing the sea from Turkey to the Greek Island of Lesvos in poorly equipped boats. This short film documents the first moments of a refugee's arrival to the coast of Lesvos, Greece.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films